Education Quality and Technological Progress in the Business Sector at Different Stages of Economic Development - Maria Majewska; Ewa Mazur-Wierzbicka; Nelson Duarte (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: To empirically investigate the relationship between education quality and technological progress in the business sector at different stages of economic development.